Manajemen Pemberdayaan Wakaf - Raden Yani Gusriani (UIN Antasari Banjarmasin, 2013)
Governments in developing countries are always trying to do the strategic steps how to increase investment or new economic resources in the country, including of course the Indonesian government. In the midst of these efforts, the endowment which is one of the cars of Islamic economics at present voluntary sector to be one of the potential alternatives which, when developed and managed in such a way to spur economic growth, which in turn can also improve the welfare of the people